1986
DOI: 10.1115/1.3239912
|View full text |Cite
|
Sign up to set email alerts
|

Design of Combustor Cooling Slots for High Film Effectiveness: Part II—Film Initial Region

Abstract: A heuristically based geometric grouping has been used to relate the geometry of practical film cooling slots of gas turbine engine combustors to the circumferential uniformity of axial velocity in the film and the average film effectiveness. To be satisfactory, the cooling performance of a slot has been shown to require a low value of this group. A study of film development has been extended to the initial region of the film where cooling performance is at its maximum. It is demonstrated that such a region ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Their data for MIX N = 0.04 and H lip /H slot = 0.4, the closest available to the current study, is plotted in Figure 11, showing a maximum x p /H of 6.2 for M = 1.05. When compared with the Sturgess and Pfeifer [8] data, x p /H is greater for all M, which may be due to the lower MIX N . The current study does demonstrate the non-linear relationship between M and x p /H, but there is insufficient data for a detailed comparison and the range of M in the current study did not show a peak value in x p /H.…”
Section: Comparison With Literaturementioning
confidence: 69%
See 2 more Smart Citations
“…Their data for MIX N = 0.04 and H lip /H slot = 0.4, the closest available to the current study, is plotted in Figure 11, showing a maximum x p /H of 6.2 for M = 1.05. When compared with the Sturgess and Pfeifer [8] data, x p /H is greater for all M, which may be due to the lower MIX N . The current study does demonstrate the non-linear relationship between M and x p /H, but there is insufficient data for a detailed comparison and the range of M in the current study did not show a peak value in x p /H.…”
Section: Comparison With Literaturementioning
confidence: 69%
“…Mukherjee [6] performed a literature survey to form a number of correlations for predicting film effectiveness and the length of the initial "potential core" region of unity effectiveness. Sturgess [7] and Sturgess and Pfeifer [8] investigated the film cooling of practical combustor slots. They formed a geometric parameter, MIX N , for characterising practical combustor slot geometries and reported the relationship between potential core length, blowing ratio, and MIX N .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the third region, convective coefficient is decreased along flow direction. Sturgess [18,19] studied the influence of blowing ratio and geometrical parameters of one-row film hole on the cooling effectiveness of cooled plate. They found that the geometrical parameters have a great influence on the cooling effectiveness of film cooling and the cooling effectiveness is decreased with increasing of blowing ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Na and Shih [11] proposed placing a ramp with a backward step upstream of the film cooling holes. Sturgess [12,13] studied the influence of the blowing ratio and geometrical parameters of a one-row film hole on cooling effectiveness. Goldstein et al [14], Schmidt and Bogard [15], and Schmidt et al [16] studied the effects of surface roughness on adiabatic effectiveness using a flat plate and saw little degradation in the adiabatic effectiveness.…”
Section: Introductionmentioning
confidence: 99%